Informasi Akuntansi dan Harga Saham Perusahaan LQ45 - Dwi Hartini Rahayu (UIR Press, 2019)
This paper examine relationship of accounting information and stock price of LQ45 firms. Earnings per share (EPS), book-value per share (BVPS) and net operating cash flow per share (NOCFPS) are used as independent variables and stock price as dependent variable. Hypothesis was tested using balanced panel data set of 23 listed companies included in the LQ45 index during 2013-2017. The result of this study shows that EPS and NOCFPS has a positive effect on stock price, while there is no evidence that BVPS has effect on stock price.